Presence, what is it good for? Exploring the benefits of virtual reality at evoking empathy towards the marginalized - Boehm, Nicholas, author; Long, Marilee, advisor; Humphrey, Michael, committee member; Shomaker, Lauren, committee member; Sivakumar, Gayathri, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2020)
This study examines the relationship between physical presence and empathy across three technology modalities: 1) virtual reality head-mount displays, 2) desktop virtual reality, and 3) text narratives with photographs displayed on a computer screen. Additionally, it examines if public support for a novel public health intervention increases when participants engage in a perspective-taking exercise designed to evoke empathy. Last, the study explores whether the benefits of empathy arousal, specifically the reduction of stereotypes toward the marginalized, depend on the technology modality used in the perspective-taking exercise. Prior studies have consistently found a positive correlation between physical presence and fear and anxiety, especially studies that have used virtual reality head-mount displays to induce presence. However, few studies have examined the relationship between physical presence and empathy. Although some studies have found a positive correlation between physical presence and empathy, these studies are few, lack comprehensive and consistent measurement, and commonly do not test the superiority of virtual reality head-mount displays at evoking empathy against more traditional technology modalities. Last, studies using virtual reality head-mount displays have found inconsistent results in how empathy affects public support and stereotypes. A 1x4 lab experiment (N = 199) was carried out to fill in these research gaps. Results include the follow: 1) physical presence was higher in the virtual reality head-mount display condition compared to the desktop virtual-reality condition and the text narrative and photograph condition; 2) physical presence was positively correlated with all four dimensions of empathy—perspective taking, fantasy, personal distress, and empathic concern; however, the relationship between presence and empathic concern was moderated by participants' mental health; 3) the amount of empathy participants experienced did not differ by experimental condition; however, cognitive empathy was lower in the control condition compared to each experimental condition; 4) public support was positively correlated with three of the four dimensions of empathy including perspective taking, fantasy, and empathic concern; 5) perceptions of stereotypes of people who inject drugs were higher in the control condition compared to the desktop virtual-reality condition and text narrative condition, but not the virtual reality head-mount display condition. Overall, this study adds to a growing body of literature exploring the benefits of virtual-reality perspective-taking exercises in three important ways. First, this study strengthens the assertion that virtual-reality head-mount displays produce more physical presence compared to desktop virtual reality and text narratives with photographs. Second, aligned with prior research, this study provides evidence of a positive correlation between physical presence and empathy arousal. However, in this study, empathy arousal appears to be increasing presence, which is a different causal pathway then the study predicted.Last, this study found that the virtual-reality head-mount display condition was the only experimental condition that did not significantly reduce stereotypes. Together, these results suggest both potential advantages and disadvantages for using virtual reality in perspective-taking exercises.
Keywords: presence; stereotypes; virtual reality; public support; empathy; supervised injection facilities